Effects of pH on Biochar's heating value during acoustic treatment. (May 2022) - Sajjadi, Baharak; Chen, Wei-Yin; Mattern, Daniell L.
Abstract: Studies have demonstrated the synergism and complexity of ultrasonic (US) treatment of biochar (BC) in H2 O with dissolved CO2 . The objective of this study is to elucidate the governing mechanistic steps of this three-phase system by a critical review of possible reactions and an experimental study of variables and kinetics, which include the effects of US energy, US amplitude and CO2 concentration on the biochar's (BC) properties. Focus is placed on the impacts of these variables on pH leading to increase in BC's higher heating value (HHV) in the early stage of US treatment. Such low-energy BC treatments involve two major groups of reactions. One starts with CO2 hydration leading to the formation of protons, which, in turn, extract alkali and alkaline earth ions, K +, Na +, Ca +2, Mg +2, etc. From BC. The second group starts with US-induced H2 O and CO2 splitting followed by formation of H, OH, CO, O, HCOOH and OCH2 leading to the fixation of C, H and O elements on BC. These processes lead to the increase in BC's specific HHV. The extent of these reactions strongly depend on the feed BC:H2 O:CO2 ratio that modulates the pH through CO2 hydration. H2 O and CO2 are the only source of H and C, respectively; thus, sufficiently low BC:H2 O and BC:CO2 ratios facilitate ion exchanges, C and H fixations, and HHV increases. Limited H2 O and CO2 cause oscillatory kinetics of this multi-component network that includes competitive reactions of different rates. The highest but un-optimized ratio of BC's-energy-gain to the US-energy-supplied observed run was 9.0. This parameter and kinetic study further suggest the synergism of adopting an ultrasonic pretreatment unit prior to BC gasification. Graphical abstract: Image 1 Highlights: Possible reactions in a biochar (BC)/H2 O/CO2 /ultrasound system are critically reviewed. Parameter and kinetic studies reveal the governing mechanistic steps leading to increase in BC's higher heating value (HHV). Sufficient H and C supplies from H2 O and dissolved CO2, respectively, secure lower pH leading to mineral extraction, and C and H fixation through ultrasonic reactions."